Charge injection promoted electrohydrodynamic instabilities in poly(3-hexylthiophene) thin films. Issue 9 (7th March 2015) - Ye, Zhi; Cui, Huina; Yang, Xiubao; Qiu, Feng
<x xml:space="preserve">Abstract</x> Electrohydrodynamic instabilities in poly(3-hexylthiophene) thin films are able to induce uniformly distributed, micrometer scale columns each composed of a spherulite.